SHARIA HOTEL ATTRIBUTES AND THEIR URGENCY FOR MUSLIM TOURISTS' NEEDS IN MAQASID SHARIAH PERSPECTIVE - Priyatmoko, Rakhman; Maulana, Addin; Oktaviyanti, Dini (Univeristas Islam Bandung, 2021)
The expansion of Sharia hotels is increasingly attracting industry players and scholars in the tourism sector. Although some researchers have focused on studying Sharia hotels' attributes, research examining these attributes deeply based on the Maslahah level in the Maqasid Shariah has not been found. By employing the literature review, this study aims to gather Sharia hotels' attributes and analyze their urgency from the Maslahah perspective using a descriptive method. The results showed that halal food availability, the prohibition of alcoholic victuals, and gender separation in fitness facilities are classified in the Dharuriyat category (fundamental). Besides, the availability of the Quran, praying amenities, and the Qibla sign are grouped in Hajiyat (secondary). Lastly, Tahsiniyat (tertiary) attributes include Ramadan special services, a particular lobby floor for women, and Muslim staff domination. Sharia hotels' other attributes can be extended for further research as long as they conform to Sharia law principles.